Evaluation of Perioperative Medication Errors and Adverse Drug Events. (January 2016) - Nanji, Karen C.; Patel, Amit; Shaikh, Sofia; Seger, Diane L.; Bates, David W.
Abstract : Background: The purpose of this study is to assess the rates of perioperative medication errors (MEs) and adverse drug events (ADEs) as percentages of medication administrations, to evaluate their root causes, and to formulate targeted solutions to prevent them. Methods: In this prospective observational study, anesthesia-trained study staff (anesthesiologists/nurse anesthetists) observed randomly selected operations at a 1, 046-bed tertiary care academic medical center to identify MEs and ADEs over 8 months. Retrospective chart abstraction was performed to flag events that were missed by observation. All events subsequently underwent review by two independent reviewers. Primary outcomes were the incidence of MEs and ADEs. Results: A total of 277 operations were observed with 3, 671 medication administrations of which 193 (5.3%; 95% CI, 4.5 to 6.0) involved a ME and/or ADE. Of these, 153 (79.3%) were preventable and 40 (20.7%) were nonpreventable. The events included 153 (79.3%) errors and 91 (47.2%) ADEs. Although 32 (20.9%) of the errors had little potential for harm, 51 (33.3%) led to an observed ADE and an additional 70 (45.8%) had the potential for patient harm. Of the 153 errors, 99 (64.7%) were serious, 51 (33.3%) were significant, and 3 (2.0%) were life-threatening. Conclusions: One in 20 perioperative medication administrations included an ME and/or ADE. More than one third of the MEs led to observed ADEs, and the remaining two thirds had the potential for harm. These rates are markedly higher than those reported by retrospective surveys. Specific solutions exist that have the potential to decrease the incidence of perioperative MEs. Abstract : This prospective observational study found that approximately 1 in 20 perioperative medication administrations, and every second operation, resulted in a medication error and/or an adverse drug event. More than one third of these errors led to observed patient harm, and the remaining two thirds had the potential for patient harm.